Suitable Locations for Industrial Setup in Urban Context: Way Forward To Meet the SDGs for Khulna City, Bangladesh (International Journal of Built Environment and Sustainability, 2021)
Industrial Site selection is one of the rudimentary decisions to expand or relocate any business start-up process. This paper aimed at finding suitable location for possible industrial site as per reaching the SDGs taking Khulna City as a case. For instance, the targeted SDGs Goal 9: Resilient Infrastructure, Sustainable Industrialization and Innovation. The research also focused on the existing locations of the industries in the Khulna city and filled the gap to propose the new locations. To achieve this, a three-stage method have been adopted. At first, the existing industries were categorized on the basis of basic/non-basic, small/large scale, input/output characteristics in geo-spatial environment. Location Quotient (LQ) technique was applied to detect basic, non-basic industries and industrial zone. Then, Analytic Hierarchy Process (AHP) was conducted to define weights of important criterion such as temperature, slope, water body, land use, city center, connectivity and structures. The calculation of Consistency Ratio (CR
Keywords: Analytic Hierarchy Process (AHP); Industrial zone; Multi Criteria Decision Analysis (MCDA); Site Suitability; Sustainable development.